Defective Flow-Migration Coupling Causes Arteriovenous Malformations in Hereditary Hemorrhagic Telangiectasia. Issue 10 (7th September 2021) - Park, Hyojin; Furtado, Jessica; Poulet, Mathilde; Chung, Minhwan; Yun, Sanguk; Lee, Sungwoon; Sessa, William C.; Franco, Claudio A.; Schwartz, Martin A.; Eichmann, Anne
Abstract : Background: Activin receptor-like kinase 1 (ALK1) is an endothelial transmembrane serine threonine kinase receptor for BMP family ligands that plays a critical role in cardiovascular development and pathology. Loss-of-function mutations in the ALK1 gene cause type 2 hereditary hemorrhagic telangiectasia, a devastating disorder that leads to arteriovenous malformations. Here, we show that ALK1 controls endothelial cell polarization against the direction of blood flow and flow-induced endothelial migration from veins through capillaries into arterioles. Methods: Using Cre lines that recombine in different subsets of arterial, capillary-venous, or endothelial tip cells, we show that capillary-venous Alk1 deletion was sufficient to induce arteriovenous malformation formation in the postnatal retina. Results: ALK1 deletion impaired capillary-venous endothelial cell polarization against the direction of blood flow in vivo and in vitro. Mechanistically, ALK1-deficient cells exhibited increased integrin signaling interaction with vascular endothelial growth factor receptor 2, which enhanced downstream YAP/TAZ nuclear translocation. Pharmacologic inhibition of integrin or YAP/TAZ signaling rescued flow migration coupling and prevented vascular malformations in Alk1 -deficient mice. Conclusions: Our study reveals ALK1 as an essential driver of flow-induced endothelial cell migration and identifies loss of flow-migration coupling as a driver of arteriovenous malformation formation in hereditary hemorrhagic telangiectasia disease. Integrin-YAP/TAZ signaling blockers are new potential targets to prevent vascular malformations in patients with hereditary hemorrhagic telangiectasia. Abstract : Supplemental Digital Content is available in the text.